Análisis e interpretación a los estados financieros de la empresa MEGACLIMA CÍA. LTDA., de la ciudad de Loja. Períodos 2015- 2016. - Jaramillo Guamán, Dayana Aracely (2018)
This thesis entitled "ANALYSIS AND INTERPRETATION TO THE FINANCIAL STATEMENTS OF THE COMPANY MEGACLIMA CÍA. LTDA., OF THE CITY OF LOJA. PERIODS 2015-2016. ", Its general objective was to perform an analysis and interpretation of the financial statements of the company" MEGACLIMA CÍA. LTDA. ", With the purpose of carrying out a study of accounting information as an indispensable component in decision-making, the preparation of financial analysis is based on bibliographic research allowing vertical and horizontal analysis and financial indicators focused on compliance with the proposed objectives. The Vertical Analysis clarifies the situation of the financial structure of the company, establishing that the Noncurrent Assets occupy a greater percentage, in relation to the total of Assets; in 2015 it has a value of 77.28% and in 2016 a value of 65.59%, a situation that is explained by being a company that provides equipment repair and maintenance services, indicating that it maintains a large investment in the account property, plant and equipment. The Horizontal Analysis allowed comparing the changes of the accounts from one period to another, showing that the Current Assets increased significantly, especially in the Banks account, obtaining a significant increase of 242.14%; due to a significant recovery of accounts and documents receivable, obtaining a relative variation of -56.49%. Non-current assets had a decrease of - 16.40%, due to the fact that in 2016 the land account was no longer part of the entity, on the other hand the account 5 called vehicles, transport equipment and mobile road equipment increased its value with a percentage of 62.38%. With respect to the income statement, an increase in its sales of 49.28% is highlighted, as well as an excessive increase in its costs and expenses, indicating that expenses amounted to 59.31%. By applying financial ratios it was possible to demonstrate that the rotation of accounts receivable is slow, obtaining a period of 183 days in 2015 and 602 days in 2016; reflecting a deficient recovery of cash, due to the contracts that it maintains with public sector institutions. There was a reduction in the net profit margin, obtaining in 2015 a value of 4.86% and in 2016 a value of 0.73%, since in 2016 the utility had a decrease of -77, 58% As a result of the analysis and interpretation of the financial statements, a report was prepared that contains a summary of the results obtained, allowing to know what has happened in the business in previous periods, obtaining a better overview of the changes presented; and in turn conclusions and recommendations that have been raised for the benefit of the company that will help plan what will be of the company from the financial and economic, through timely decision making, which will be exposed in the capacity to generate greater profitability .